9 [videorecording (DVD)] - Burton, Tim, 1958-; Acker, Shane; Plummer, Christopher; Landau, Martin, 1928-2017; Reilly, John C., 1965-; Glover, Crispin; Connelly, Jennifer; Wood, Elijah, 1981-; Kane, Tom (Universal Studios Home Entertainment, 2009)
When rag doll 9 first comes to life, he finds himself in a post-apocalyptic world where all humans are gone. It is only by chance that he discovers a small community of others like him taking refuge from fearsome machines that roam the earth intent on their extinction. Despite being the newest member of the group, 9 convinces the others that hiding will do them no good. They must take the offensive if they are to survive and they will need to discover why the machines want to destroy them in the first place. The very future of civilization may depend on them.